The role of space as recreated in the discourse identity construction of Mapuche adolescents from Temuco and Santiago (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This article describes the connection between Mapuche rural cultural spaces and those re-created in urban areas and their connection with the construction of ethnic identity in urban Mapuche adolescents. This is a qualitative and descriptive study and the data is analyzed through the approach of discourse analysis of discursive psychology (Edwards y Potter, 1998, 2000) and considers the notion of place identity by Proshansky (1978). The research population were thirty Mapuche adolescents living in Santiago and thirty living in Temuco. These adolescents were interviewed by a Mapuche interviewer. The findings reveal that the re-created urban cultural spaces fulfill a mediating role in the change from original places to new ones (Proshansky et al., 1983), which allows these adolescents to reinforce their ethnic identity construction.
Keywords: Recreated spaces; Place-identity; Mapuche identity; Mediating role; Discourse analysis